ANALISIS Hg2+ DENGAN MENGGUNAKAN NANOPARTIKEL PERAK (NPP) SEBAGAI INDIKATOR KOLORIMETRI DENGAN METODE SPEKTROFOTOMETRI - Renaldi Adriansyah; M. Lutfi Firdaus; Elvinawati Elvinawati (ALOTROP, 2017)
[ANALYSIS OF Hg2+ USING NANOPARTIKEL METAL (NPP) AS A COLORIMETRY INDICATOR WITH SPECTRUMFOTOMETRY METHOD]. Mercury (Hg) is heavy metal with high toxicity that often pollutes the aquatic environment. Concentration of Hg (II) ions is usually determined by using ICP-MS and AAS but because its price relatively expensive an alternative is needed to determine concentration of Hg. Therefore, the purpose of the study was to conduct synthesis of silver nanoparticles (NPP) by utilizing extract of Phyllanthus acidus ceremin fruit as a colorimetric indicator for alternative analysis concentration of Hg metal in digital image. Bio NPP used as a colorimetric indikator of Hg metal in this study was synthesized at optimum condition. The optimum condition of Bio NPP synthesis was obtained on the ratio of extract volume of P. acidus  fruit and AgNO3 1: 1 and the duration of exposure to sunlight for 1 hour.The formed Bio NPP knew to be selective against Hg (II) metal ions characterized by the change of Bio NPP color from brownish yellow to clear. In addition, the Bio NPP that has been synthesized  in this study can be used as a colorimetric indicator of Hg metal analysis using spectrofotometer uv-vis with detection limit  7.56 ppb.